2003
DOI: 10.1161/01.cir.0000068313.67758.4f
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Myocardial Function Assessed by Tissue Velocity, Strain, and Strain Rate Tissue Doppler Echocardiography in Patients With AL (Primary) Cardiac Amyloidosis

Abstract: Background— AL amyloidosis with heart failure is associated with decreased longitudinal myocardial contraction measured by pulsed tissue Doppler imaging. We sought to clarify whether new modalities of myocardial strain Doppler (change in length per unit length) or strain rate (the temporal derivative of strain) were more sensitive than tissue Doppler and could detect early regional myocardial dysfunction before the onset of congestive heart failure (CHF) in patients with AL (primary) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
232
0
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(259 citation statements)
references
References 23 publications
16
232
0
11
Order By: Relevance
“…Therefore, the assessment of PM contractility is considered to be problematic through the use of tissue velocity imaging only. It has also been reported that LV contraction abnormalities identified by myocardial strain imaging precede the onset of congestive heart failure, but it is not apparent by tissue velocity imaging in patients with cardiac amyloidosis [15]. The present study indicates that peak systolic strain in the posteromedial PM correlated positively and negatively with peak systolic strain in the LV I/P wall and LVEF, respectively, but did not correlate with the severity of MR.…”
Section: Discussionsupporting
confidence: 47%
“…Therefore, the assessment of PM contractility is considered to be problematic through the use of tissue velocity imaging only. It has also been reported that LV contraction abnormalities identified by myocardial strain imaging precede the onset of congestive heart failure, but it is not apparent by tissue velocity imaging in patients with cardiac amyloidosis [15]. The present study indicates that peak systolic strain in the posteromedial PM correlated positively and negatively with peak systolic strain in the LV I/P wall and LVEF, respectively, but did not correlate with the severity of MR.…”
Section: Discussionsupporting
confidence: 47%
“…In the nondialysis population, GLS is proved as a more reliable and sensitive parameter for representing LV systolic function in patients with cardiomyopathies, advanced-stage CKD, or HF with preserved LVEF (11,12,(27)(28)(29)(30). Less negative GLS is also proved as a powerful predictor of all-cause mortality in the general population (9), and is reported to be useful in the preclinical diagnosis of a number of other cardiomyopathies, including diabetes, hypertrophic cardiomyopathy, and amyloidosis (28)(29)(30). In these cardiomyopathies, only GLS precedes any clinical evidence of overt systolic dysfunction, suggesting that abnormal GLS may represent an early stage of abnormal LV geometry and function.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in strain echocardiography [59], elevation of the N terminal Pro brain natriuretic peptide (NT-Pro BNP) [60], and elevation of cardiac troponins [61] are seen in a wide variety of cardiac disorders, and the sensitivity and specificity of these tests compared with echocardiography have not been evaluated sufficiently for these variables to be incorporated as criteria of cardiac involvement. Myocardial amyloid is excluded by normal values of NT-Pro BNP [62].…”
Section: Heartmentioning
confidence: 99%